Enhancing efficiency of using water due to explosive breakup of liquid drop; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Borisova A. G. Anastasia; Gumerov V. M. Vladislav; Piskunov M. V. Maksim Vladimirovich; Ushmaev D. V. Denis (2017, 2017)
Title screen